A simulation-based approach to characterise melt-pool oscillations during gas tungsten arc welding. (January 2021) - Ebrahimi, Amin; Kleijn, Chris R.; Richardson, Ian M.
Highlights: High-fidelity numerical simulations are performed to predict melt-pool oscillations during gas tungsten arc welding. Molten metal oscillation is studied for steady-current and pulsed-current GTA welding. Time-frequency analysis based on a wavelet transform is conducted to study melt-pool oscillatory behaviour. During transition from partial to full penetration state, two dominant frequencies coexist in the time-frequency spectrum. Applying the proposed simulation-based approach, the need of triggering action is expendable. Abstract: Development, optimisation and qualification of welding and additive manufacturing procedures to date have largely been undertaken on an experimental trial and error basis, which imposes significant costs. Numerical simulations are acknowledged as a promising alternative to experiments, and can improve the understanding of the complex process behaviour. In the present work, we propose a simulation-based approach to study and characterise molten metal melt pool oscillatory behaviour during arc welding. We implement a high-fidelity three-dimensional model based on the finite-volume method that takes into account the effects of surface deformation on arc power-density and force distributions. These factors are often neglected in numerical simulations of welding and additive manufacturing. Utilising this model, we predict complex molten metal flow in melt pools and associated melt-pool surface oscillations during both steady-current and pulsed-current gas tungsten arc welding (GTAW). An analysis based on a wavelet transform was performed to extract the time-frequency content of the displacement signals obtained from numerical simulations. Our results confirm that the frequency of oscillations for a fully penetrated melt pool is lower than that of a partially penetrated melt pool with an abrupt change from partial to full penetration. We find that during transition from partial to full penetration state, two dominant frequencies coexist in the time-frequency spectrum. The results demonstrate that melt-pool oscillations profoundly depend on melt-pool shape and convection in the melt pool, which in turn is influenced by process parameters and material properties. The present numerical simulations reveal the unsteady evolution of melt pool oscillatory behaviour that are not predictable from published theoretical analyses. Additionally, using the proposed simulation-based approach, the need of triggering the melt-pool oscillations is expendable since even small surface displacements are detectable, which are not sensible to the current measurement devices employed in experiments.